Multiplicity-dependent activation of a serine protease-dependent cytomegalovirus-associated programmed cell death pathway - McCormick, A. Louise (2012)
At a low MOI (≤ 0.01), cytomegalovirus-associated programmed cell death terminates productive infection via a pathway triggered by the mitochondrial serine protease HtrA2/Omi. This infected cell death is associated with late phase replication events naturally suppressed by the viral mitochondrial inhibitor of apoptosis (vMIA). Here, higher MOI (ranging from 0.1 to 3.0) triggers cell death earlier during infection independent of viral DNA synthesis. Thus, MOI-dependent activating signals early, at high MOI, or late, at low MOI, during replication promote serine protease-dependent death that is suppressed by vMIA. Treatment with an antioxidant targeting reactive oxygen species (ROS) or the serine protease inhibitor N-alpha-p-tosyl-L-lysine chloromethyl ketone (TLCK) delays cell death, and the combination has an additive impact. These studies identify serine proteases and ROS as important factors triggering programmed cell death induced by vMIA-deficient virus, and show that this death pathway occurs earlier and reduces viral yields as the MOI is increased.